Electrogenerated base-promoted synthesis and antimicrobial activity of 2-imino-1, 3-thiazolidin-4-one derivatives. (3rd July 2016) - Haouas, Beya; Saied, Taieb; Ayari, Hanen; Arfaoui, Youssef; Benkhoud, Mohamed Lamine; Boujlel, Khaled
ABSTRACT: Electrogenerated cyanomethylanions obtained by reduction of dry acetonitrile at a steel grid cathode were used to promote the addition of ethyl bromoacetate to thiourea derivatives. The reaction yields the corresponding 2-imino-1, 3-thiazolidin-4-one. The reaction pathway was discussed based on the kinetic and thermodynamic data obtained by computational methods. In addition, the biological activity of these new compounds was also investigated. GRAPHICAL ABSTRACT: